Behavior of CFRP-confined recycled aggregate concrete under axial compression. (15th May 2016) - Chen, G.M.; He, Y.H.; Jiang, T.; Lin, C.J.
Highlights: FRP confinement is effective for recycled aggregate concrete (RAC). The behavior of FRP-confined RAC is similar to FRP-confined normal concrete. The replacement ratio has a limited effect on the FRP confinement effectiveness. Abstract: Over the past decade, recycled aggregate concrete (RAC) has attracted world-wide research interests due to its environmental and economic significance. However, RAC has mainly been limited to non-structural uses, largely due to the disadvantages of RAC (e.g. lower strength/stiffness, larger creep and shrinkage, poorer durability) compared to natural aggregate concrete (NAC). A possible approach of using RAC in structural compressive members is to confine RAC in a fiber reinforced polymer (FRP) jacket as the compressive performance of concrete can be significantly improved through confinement. To understand the compressive behavior FRP-confined RAC, this paper presents the results of a large number of compression tests on CFRP-confined RAC cylinders whose major test parameters are the replacement ratio of coarse aggregate and the CFRP jacket stiffness. The test results show that the replacement ratio does not have a significant effect on the FRP confinement effectiveness. The compressive behavior of FRP-confined RAC is similar to that of FRP-confined NAC and can be reasonably approximated by existing stress–strain models for FRP-confined NAC.